Towards the development and application of representative lexicographic corpora for the Gabonese languages - Soami, Leandre Serge (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DLitt (Afrikaans and Dutch))--University of Stellenbosch, 2010.